Oleander Aphid, Aphis nerii Boyer de Fonscolombe (Insecta: Hemiptera: Aphididae) - Heather J. McAuslane (EDIS, 2004)
The oleander aphid, Aphis nerii Boyer de Fonscolombe, sometimes called the milkweed aphid, is a common pest of several important ornamental plants in the families Apocynaceae and Asclepiadaceae. This bright yellow aphid with black appendages is commonly found in Florida feeding on oleander, Nerium oleander, milkweeds, such as butterfly weed, Asclepias tuberosa, and scarlet milkweed, Asclepias curassavica, and wax plant, Hoya carnosa. This document is EENY-247, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November, 2001.